The role of regular liver function monitoring in antituberculosis drug-induced liver injury. Issue 7 (July 2019) - Chang, Tien-En; Huang, Yi-Shin; Su, Wei-Juin; Perng, Chin-Lin; Huang, Yi-Hsiang; Hou, Ming-Chih
Abstract : Background: Antituberculosis (TB) drug-induced liver injury (ATLI) is a common adverse effect of anti-TB drugs. Whether regular monitoring of liver function can ameliorate ATLI has been widely debated. The current study aimed to investigate the liver test monitoring status of patients receiving anti-TB treatment in Taiwan, as well as the impact of scheduled liver function monitoring on the risk of ATLI. Methods: Patients who received anti-TB treatment at our hospital between 2009 and 2017 were enrolled for retrospective analysis. Results: A total of 1062 patients were included, and of them 469 (44.2%) received regular liver function monitoring (good monitoring group). ATLI was recognized in 100 (9.4%) patients. The good monitoring group detected more ATLI cases early compared with the poor monitoring group (14.7% vs 5.2%, and 21.4 vs 61.6 days, p < 0.01), with a lower peak serum alanine aminotransferase (276.1 vs 507.1 IU/L, p = 0.05). Conclusion: In the current study, less than half of all patients who received anti-TB drugs had their liver function monitored regularly. Scheduled monitoring of liver function could facilitate the early identification of more ATLI cases, thus leading to less liver injury. The implementation of periodic liver function monitoring tests in patients receiving anti-TB treatment should be re-emphasized and encouraged.